2009
DOI: 10.1002/cjg2.1379
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Correction Models for Tidal Gravity in Chinese Continent

Abstract: Accurate correction models for tidal gravity in Chinese continent are developed by using the recent theoretical and experimental models for the Earth's tidal gravity, in which the loading effects of the global and local ocean tides are combined. The relative difference of tidal gravity variations induced from different Earth's tidal gravity models is less than 0.06%. The ocean tide loading effects are about 4% of the total tidal gravity in coastal area while they are about 1% in inland. The difference between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Among these tidal waves, M 2 has the largest amplitude for the loading vector of oceanic tides of 4.122 nm s , which is only about 0.6% of the observed amplitude for gravity tides. In the diurnal frequency band, the strongest effect of oceanic tide loads on gravity tides is that for K 1 , whose amplitude is only 1.667 nm s For the other tidal waves with lower amplitudes, the oceanic tide loading vectors were obtained by interpolating or extrapolating in the frequency domain [34]. The loading vector of the oceanic tide for wave M 4 was obtained using the co-tide maps provided by global oceanic tides model Fes2004.…”
Section: Loading Effects Of Oceanic Tides and Atmospherementioning
confidence: 99%
“…Among these tidal waves, M 2 has the largest amplitude for the loading vector of oceanic tides of 4.122 nm s , which is only about 0.6% of the observed amplitude for gravity tides. In the diurnal frequency band, the strongest effect of oceanic tide loads on gravity tides is that for K 1 , whose amplitude is only 1.667 nm s For the other tidal waves with lower amplitudes, the oceanic tide loading vectors were obtained by interpolating or extrapolating in the frequency domain [34]. The loading vector of the oceanic tide for wave M 4 was obtained using the co-tide maps provided by global oceanic tides model Fes2004.…”
Section: Loading Effects Of Oceanic Tides and Atmospherementioning
confidence: 99%
“…Chen et al., 2019; Wan et al., 2019). However, accompanying with the accumulation of more and more seismic data, some problems about the timing anomalies have been found recently, and relevant solutions have been proposed for Chinese OBS (Li et al., 2023; Wang et al., 2016; Zhang et al., 2018, 2019.). These timing errors in OBS data will be a limiting factor in other researches, such as the high‐precision earthquake locations and associated tomographic inversions for velocity structure.…”
Section: Introductionmentioning
confidence: 99%
“…Sibson used it to explain cyclic movements of such faults in Quebec area. Zhou et al [10] suggested movements of these faults at Longmenshan were related to highly geo-pressured fluids within them, which triggered the slipping movement of these faults and was a requirement which induced Wenchuan earthquake.…”
mentioning
confidence: 99%